2015
DOI: 10.1002/14651858.cd004437.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolytic therapy for pulmonary embolism

Abstract: There is low quality evidence that thrombolytics reduce death following acute pulmonary embolism compared with heparin. Furthermore, thrombolytic therapies included in the review were heterogeneous. Thrombolytic therapy may be helpful in reducing the recurrence of pulmonary emboli but may cause more major and minor haemorrhagic events and stroke. More high quality double blind RCTs assessing safety and cost-effectiveness are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 71 publications
2
24
1
1
Order By: Relevance
“…Logistic regression analysis showed a beneficial effect of thrombolysis. This finding is similar to previously reported data [20]. There is good evidence on superiority of thrombolysis to heparin alone to accelerate lysis of emboli and restore hemodynamics and RV function [20, 21].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Logistic regression analysis showed a beneficial effect of thrombolysis. This finding is similar to previously reported data [20]. There is good evidence on superiority of thrombolysis to heparin alone to accelerate lysis of emboli and restore hemodynamics and RV function [20, 21].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is similar to previously reported data [20]. There is good evidence on superiority of thrombolysis to heparin alone to accelerate lysis of emboli and restore hemodynamics and RV function [20, 21]. Most patients respond favorably to thrombolysis, as judged by clinical and echocardiographic improvement within 36 hours [22].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Another parameter that can be used for resuming unfractionated heparin is serum fibrinogen concentration, which should be above 100 mg/dL. 15,16,44 …”
Section: Systemic Fibrinolysis Doses In Ptementioning
confidence: 99%
“…12,13 As a result, current consensus statements on management of PTE are clear and objective in stating that the only precise indication for using SFT is in patients with HI. 3,14,15 The ninth consensus of the American College of Chest Physicians (ACCP), in 2012, suggested that SFT should only be used in the absence of HI in severe PTE with RV failure and even this recommendation was based on a very weak evidence level (2C) and was subject to case-by-case assessment of risks and benefits. 14 A recently-published study described experience with use of SFT in 20% of American hospitals.…”
Section: Introductionmentioning
confidence: 99%